Anesthetic Management of Children with KBG Syndrome and Novel Use of Sacral Erector Spinae Block: A Case Report - Sana Y. Hussain; Nishant Patel; Anju Gupta; Nupur Pandya (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
KBG syndrome is a rare genetic disorder manifested by craniofacial dysmorphism, skeletal abnormalities, short stature, and developmental delay. The anesthetic management may be challenging due to associated craniofacial and other skeletal abnormalities and possible cardiac defects. We report a case of a 2-year-old child with KBG syndrome presenting with a chylothorax and an abscess on the lower back over the coccygeal region. The child was posted for fistula tract excision and coccygectomy and received sacral erector spinae block as analgesic modality.